Determination of factor influencing man’s facial attractiveness considered as mr right: a 2k factorial design approach / Noor Aisyah Idris - Idris, Noor Aisyah (2014)
They are several causes of women delaying marriage such as education, job opportunities, financial problem and others. However, the highest percentage of reason women delaying marriage is no suitable candidates. Interestingly, the percentages of unmarried men compared to women are much higher. This phenomenon is relevant to understand whether men are not physically attractive. This study aimed to determine which characteristic of man’s facial characteristic that women considered as Mr Right and the interaction effect of man’s facial characteristic that women are attracted. In addition, this study is also interested to compare whether non-science and science student have different preferences towards man face and identify the best model to determine man’s facial attractiveness for both non-science and science student. This study has been designed and analysed using 2k factorial design. By using picture-based as an instrument, 320 observations were collected for each group among UiTM student. Forty selected women were given 16 different pictures of men’s face to rate the attractiveness of men’s face. Each pictures having different characteristic or factors suggested by factorial design using design matrix. There are four factors used which are beard, hair, skin colour and glasses. Factorial analysis is used to examine which factors are influencing the attractiveness of man face. It is found that beard, hair and glasses are significantly attractive to the nonscience students. The significant two combination factors are beard and hair; beard and skin colour; hair and skin colour; hair and glasses. The three combinations factors significantly attractive are beard, hair and glasses; beard, skin colour and glasses; and hair, skin colour and glasses. Likewise, science student feels that all four main factors which are beard, hair, skin colour and glasses are important factor in determine facial attractiveness. The two combination factors shows that only two pairs are significant which are beard and glasses; hair and glasses. There are no three combination factors significant to the model. However, the four combination factor is important in determining man’s facial attractiveness. Result of the analysis shows that different background of study have different preferences towards man’s face.